PENGARUH TENUR KAP, REPUTASI KAP DAN ROTASI KAP TERHADAP KUALITAS AUDIT - Nurul Fitri Nadia (Jurnal Akuntansi Bisnis, 2015)
The researchs objective is to investigate the effect of accounting firmstenure, reputation , and the rotation of accounting firms on audit quality. This study uses 2008-2012 data from Indonesia Stock Exchange and adopts Jones models to calculate discretionary accruals that has been widelu used as proxy for audit quality. Multiple regression analysis is applied on the data . The result shows that The longer the tenure, the higher accruals discretionary, companies audited by big four accounting firms have higher discretionary accruals , and firms that experienced rotation has highher discretionary accruals